2021
DOI: 10.1063/5.0041003
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Li complex emission in ZnO

Abstract: In this work, we report on three new extremely sharp emission lines in zinc oxide (ZnO) related to iron–lithium complexes. The identification is based on a comparison of hydrothermally grown ZnO with high lithium concentration and a lithium-free sample grown by methane based chemical vapor deposition, which both were implanted with iron. After annealing in a mixed oxygen/argon atmosphere at 800°C, the lithium-free sample showed no additional lines besides the well-known emission at 693nm (1.78734eV), whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The strong and sharp red emission obtained around 734nm for CS0 and CS1 samples (Fig. 6) can be attributed to the stronger admixture of p-states of the neighboring oxygen atoms into the Fe 3+ d-states by virtue of the shorter lattice parameter in the presence of chloride ions as given in reports [21] which also confirms the proportion of AgCl in CS0 and CS1 given in XRD and EDAX results. A weak green emission around 533nm is due to the recombination of electrons deeply trapped in oxygen vacancies in the zinc ferrite with photogenerated holes.…”
Section: Diffusesupporting
confidence: 78%
“…The strong and sharp red emission obtained around 734nm for CS0 and CS1 samples (Fig. 6) can be attributed to the stronger admixture of p-states of the neighboring oxygen atoms into the Fe 3+ d-states by virtue of the shorter lattice parameter in the presence of chloride ions as given in reports [21] which also confirms the proportion of AgCl in CS0 and CS1 given in XRD and EDAX results. A weak green emission around 533nm is due to the recombination of electrons deeply trapped in oxygen vacancies in the zinc ferrite with photogenerated holes.…”
Section: Diffusesupporting
confidence: 78%
“…38 ZnO nanorods with 2.05% Fe and 1.95% Li exhibit strong luminescence due to dopant defects, and band-to-band transition and luminescence are strongly suppressed due to more efficient recombination through deep levels associated with Li and Fe. The emission band covering the range from 2.0 eV (600 nm) to 1.7 eV (730 nm) is associated with a series of differently charged complexes Fe Zn −Li Zn and Li−O complexes 32,55 as well as complexes Fe Zn 3+ ions. 56 Velaźquez et al 57 showed that the NIR emission band covering the range from 1.7 eV (730 nm) to 1.4 eV (880 nm) arises due to radiative transitions in Li−Li nanoclusters located in ZnO interstices.…”
Section: ■ Resultsmentioning
confidence: 99%
“…XAS research by Giuli et al 30 demonstrated aliovalent substitution of Fe 3+ for Zn 2+ in Zn 0.9 Fe 0.1 O samples accompanied by the formation of cationic vacancies or interstitial oxygen around incorporated Fe 3+ ions for charge compensation. Kutin et al 31 and Muller et al 32 reported EPR and photoluminescence research on Fe 3+ −Li + complexes in ZnO, where Fe 3+ and Li + ions substitute for Zn 2+ sites in the same basal plane, and Fe 3+ and Li + ions substitute for Zn 2+ in an axial cationic site and one of the nearest basal plane sites, and vice versa. Regarding lithiation of Zn 0.9 Fe 0.1 O, Giuli et al 33 wrote that cationic vacancies play a crucial role upon initial lithiation leading to partial reduction of Fe 3+ to Fe 2+ ions.…”
Section: ■ Introductionmentioning
confidence: 99%